The fallen man - Hillerman, Tony (Hillerman, Tony. Leaphorn & Chee novel., 1997)
Navajo policemen Joe Leaporn and Jim Chee are on the case involving the remains of a man which have been on the ledge under the peak of Ship Rock for eleven years.